UTILIZATION OF DIGITAL TECHNOLOGY IN LEARNING ACTIVITIES FOR CIKAL CENDEKIA ISLAMIC FULLDAY SCHOOL - Chandra Sagul Haratua; Haura Putri Listy Dief; Nur Aisah; Poppy Guswita; Serafim Christina; Yuneva Yuneva (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2024)
Technology has become a tool which could help people with activities of many kinds, including education. Our big dream for the future is that digital technology could be implemented and spread equally for education in Indonesia. A system was created to automatically get the score when the students submit their tasks or to learn more information or students just access the system and find e-books. The research discussion aims to provide an overview and results obtained from this research. Interviews and observations are the instruments and data collection methods used in this research. The subject selection technique in this research uses purposive sampling. This technique is chosen so that the subjects are selected in accordance with the research objectives. The subject criteria in this research are 1) Academic teachers 2) All 8th grade students 3) Teachers aged between 20 until 45 years old. The results of this research is all academic teachers in SMP Cikal Cindekia Fullday Islamic School used digital technology in learning activity. In the implementation, the benefits of digital technology can be felt by both students and teachers. But, teachers must give more attention when the students use digital technology.